Evaluation of cutoff scores for the Parkinson's disease sleep scale‐2. (17th November 2014) - Suzuki, K.; Miyamoto, T.; Miyamoto, M.; Suzuki, S.; Numao, A.; Watanabe, Y.; Tatsumoto, M.; Sakuta, H.; Watanabe, Y.; Fujita, H.; Iwanami, M.; Sada, T.; et al.
<x xml:space="preserve">Abstract</x> Background The Parkinson's Disease Sleep Scale (PDSS)‐2 is a recently developed tool for evaluating disease‐related nocturnal disturbances in patients with Parkinson's disease (PD). However, its cutoff score has not been clinically assessed. We determined the optimal cutoff score of the Japanese version of the PDSS‐2. Methods Patients with PD (n = 146) and controls (n = 100) completed the PDSS‐2 and the Pittsburgh Sleep Quality Index (PSQI). Poor sleepers were defined as having global PSQI scores >5. Optimal cutoff scores for determining poor sleepers were assessed using the receiver operating characteristic curve. Results A PDSS‐2 total score ≥14 exhibited 82.0% sensitivity and 70.6% specificity, whereas a PDSS‐2 total score ≥15 provided 72.1% sensitivity and 72.9% specificity in distinguishing poor sleepers (PSQI score >5) from good sleepers (PSQI ≤5). Nocturnal disturbances were more frequently observed in patients with PD than in controls (PDSS‐2 total score ≥14 or ≥15; 51.4% vs 20%; 45.9% vs 19%). Nocturnal disturbances were associated with higher Hoehn and Yahr stages and Unified Parkinson's Disease Rating Scale motor scores, impaired quality of life, daytime sleepiness, and depressive symptoms. Conclusion We suggest that PDSS‐2 total scores ≥15 are useful for detecting poor sleepers among patients with PD.